A Fight for Justice: The Compelling Story of Temporary Foreign Workers & Human Rights - Barrett, Joe (Ronsdale Press, 2026)
How migrant workers, with the support of Canadian unions, won justice in a landmark court decision. In April 2006, 42 Latin Americans landed in Vancouver to excavate tunnels for the Canada Line Skytrain. They thought they'd won the lottery with promised wages far above what they would earn at home. But the reality was miserable wages, unpaid overtime and inadequate living conditions. It was the beginning of the Canadian construction industry's reliance on migrant workers and the treatment of temporary foreign workers has made headlines ever since. Author Joe Barrett, fluent in Spanish and a researcher for BC Building Trades unions, first spoke to three of the Costa Rican workers through a chain link around the worksite. They confirmed the low wages. He shares his unique insider perspective as he joined the team of union organizers and became a liaison between workers, union officials and lawyers throughout the court battles. The workers' resentment grew in the face of employer lies, intimidation, coercion and prejudice. Most of them came from a group of villages in central Costa Rica. They grew up together, sharing a background of poverty and hardship. These common bonds gave them the courage they needed to face fears of employer retaliation as they organized, which resulted in a successful vote for union certification, a first for temporary foreign workers in the Canadian construction industry. But their victory was short-lived and their unity was broken by a series of employer "sticks and sweeteners." The fight for fairness continued at the BC Labour Relations Board (BCLRB) and, ultimately, at the BC Human Rights Tribunal in a race against time before the workers left Canada with the completion of the tunnels. In 2008, the tribunal delivered a triumphant decision, a landmark case in the evolving issue of global migration. Workers were awarded $2.4 million to compensate for discrimination based on country of origin; for wages, inferior accommodations, meals and expenses and injury to dignity and feelings. A Fight for Justice is an inspiring story of collective action and relationships across progressive communities in Canada and Latin America and offers a remarkable story of migrant workers successfully fighting for fairness and equality. --Publisher's description

Small Town Deal The Life and Death of Renfrew Woollen Mills, 1917–1953 - Campbell, J. Peter (Working Canadians: Books from the CCLH, 2026)
To be published: October 2026. Sir John A. Macdonald’s National Policy was meant to foster the domestic production of consumer goods and, in the process, ensure steady jobs at good wages. In reality, in small towns like Renfrew, Ontario women workers laboured for unconscionably low wages, and men worked staggeringly long hours. They suffered largely in silence, their exploitation hidden by a myth of small town community that denied their class standing. In this book, Peter Campbell brings to life the untold story of how small-town workers in the Renfrew Woollen Mills both benefitted from and were exploited by a National Policy that survived on their unseen labour and silent sacrifices. The “small town deal” rested on the expectation that workers would be seen but not heard while employers maintained labour harmony through paternalistic ideals and practices. Focusing on Catholic owners and Catholic workers, this book introduces a different Ontario, one in which the Catholic Church plays a key role in fostering worker acceptance of their class standing. Campbell details both the heyday of this moral economy and the challenge to it in the form of the 1937 strike, then a “company union,” and later the arrival of the Textile Workers Union of America. Renfrew’s small town deal survived the coming of the international union movement, but could not survive Cold War anti-Communism and the Liberal Party’s dismantling of the woollen textile industry as part of the creation of a new post-war economic order. The era of the National Policy and the small town deal is gone, but the contributions and the struggles of the workers who made small towns like Renfrew places where things were made live on. --Publisher's description

The Incognito Reporter and the On-to-Ottawa Trek - Dupuis, Michael (Friesen Press, 2026)
At the height of the Great Depression, 2,000 young, single, unemployed and homeless men decided to ride boxcars from Vancouver to Ottawa to seek work and wages from Prime Minister "Iron Heel" R.B. Bennett. Their undertaking became the On-To-Ottawa Trek. Vancouver Advocate cub reporter Mark Hunter is given the perilous assignment of infiltrating the Trek. Once accepted into the journey, can he remain incognito? Can he endure the odyssey's hardships and dangers? Also, can he survive the Trek's violent ending? Most important, can he provide objective and accurate reporting of the historic event? --Publisher's description

Confronting the Resurgent Right - Edelson, Miriam (University of Manitoba Press, 2026)
Exposing the deep roots and new threats of Canada's regressive right. Over the past decade, we have witnessed the global mainstreaming of hate as false narratives and conspiracy theories about equity and inclusion, immigration, COVID-19 and vaccinations, and the “gay agenda” have become permissible talking points among right-wing politicians, pundits, and influencers. In Confronting the Resurgent Right, scholars and activists take Canada’s 2022 “Freedom Convoy” as a recent manifestation of deep-rooted extremism. Providing intersectional commentary on the resurgence of the right, they demonstrate how its ideology permeates and shapes the structures of our society. Balancing evidence-based research with careful analysis of the genesis and methods of the right, this volume models pathways of resistance and charges us to work together to expose and counter the regressive forces that spew hate. --Publisher's description

Health and Safety in Canadian Workplaces - Foster, Jason; Cake, Susan; Barnetson, Bob (Open paths to enriched learning, 2026)
Workplace injuries happen every day and can profoundly affect workers, their families, and the communities in which they live. This textbook is for workers and students looking for an introduction to injury prevention on the job. It offers an extensive overview of central occupational health and safety (OHS) concepts and practices and provides practical suggestions for health and safety advocacy. Foster, Cake, and Barnetson bring the field into the twenty-first century by including discussions of how precarious employment, gender, and ill-health can be better handled in Canadian OHS. Although they address the gendered and racialized dimensions of new work processes and structures in contemporary workplaces, Foster, Cake, and Barnetson contend that occupational health and safety can only be understood if we acknowledge that workers and employers have conflicting interests. Who identifies what workplace hazards should be controlled is therefore a product of the broader political economy of employment and one that should be well understood by those working in the field. The newly revised second edition updates key information and discusses OHS topics related to emerging issues such as COVID-19 and climate change. It offers an expanded discussion of chemical and biological hazards and provides all-new learning activities and exercises. --Publisher's description

Nouveaux dialogues et conversations émergentes en relations industrielles = New Dialogues and Emerging Conversations in Industrial Relations - Foster, Jason; Jalette, Patrice; Merkouche, Wassila; Yao, Yao (Presses de l'Université Laval, 2026)
Adoptant un format original axé sur le dialogue et la conversation, cet ouvrage collectif se situe dans la tradition des travaux en relations industrielles – un champ disciplinaire étudiant les problèmes variés associés au travail et à l’emploi. Il jette un regard d’ensemble sur les nouveaux enjeux émergents concernant le futur des milieux de travail et aborde des sujets tels que la crise climatique, le télétravail, la diversité, l’équité et l’inclusion au travail, l’avenir du syndicalisme et les droits des travailleurs. / With an original format centred on dialogue and conversation, this book is rooted in the tradition of industrial relations research, a disciplinary field that studies diverse problems associated with work and employment. As a collaborative work that takes a broad look at new and emerging issues concerning the future of workplaces, it addresses topics such as the climate crisis, telework, diversity, equity, and inclusion at work, the future of unionism, and workers’ rights. --Publisher's description / Résumé de l'éditeur

The Long Sixties: Stories from the New Left - Harding, Jim (Fernwood Publishing, 2026)
The sixties were not just “sex, drugs, and rock and roll.” Social movements aimed at overcoming patriarchy, colonialism, and corporate capitalism were equally part of the sixties revolution. These movements are still very much alive. In The Long Sixties, seven veteran political activists from the sixties, all still engaged in campaigns and organizations across Canada, tell their stories of transformational activism. What could veteran activists from the sixties teach about activism? In addition to telling their stories — how they got involved, why they stay involved, how they persevered into their twilight years — they also critically reflect on their victories and defeats, their personal and political challenges, what they learned, and how their perspectives deepened and changed along the way. This book provides hope, chronicling the significant gains — in advancing peace, international human rights, Indigenous rights, women’s and 2SLGBTQ+ rights, workers’ rights, and environmental protection. Weathered voices open an intergenerational conversation about social solidarity and transformation to address the grave crises we face globally and nationally, including climate catastrophe, escalating warfare, extreme wealth inequality, ethno-nationalism, and a heightened continental threat to Canada’s sovereignty. -- Publisher's description

Roles of Resistance: Game Plans for Teachers and Troublemakers - Harter, John-Henry; Leier, Mark (James Mark) (Between the Lines, 2026)
Designed for educators and facilitators from the union hall to the lecture hall, Roles of Resistance: Game Plans for Teachers and Troublemakers outlines revolutionary lesson plans on how to fight the power with people power. The thirteen lesson plans in this book created by John-Henry Harter and Mark Leier can be used independently or combined to create a semester-long course. Sections include units on teaching political economy, labour history, and social activism based on democratic, experiential teaching, including role-plays, simulations, and games. The tried and tested classroom activities in this teacher's guide--successfully applied in high schools, universities, and union classrooms--are bound to create a vibrant learning experience, enriching debates, and providing the main tool we need to change the world: collective action. --Publisher's description

The Red Baron of IBEW Local 213 : Les McDonald, Union Politics, and the 1966 Wildcat Strike at Lenkurt Electric - McDonald, Ian (Athabasca University Press/Canadian Committee on Labour History, 2026)
The “Red Baron” from Local 213 of the International Brotherhood of Electrical Workers (IBEW) was Les McDonald, once a firebrand Communist activist and the youthful leader of the left faction within the Vancouver electrical workers’ union. His fate would be intertwined with the Lenkurt Electric strike of 1966, a wildcat strike that led to the imprisonment of four trade union leaders. Following his involvement as a long-time trade unionist, McDonald went on to be better known for his dedication to the establishment of triathlon as an official sport of the Olympic Games. However, McDonald’s important role in Local 213 and the Lenkurt strike—a watershed moment in Canadian labour history—was, until now, the untold story of the first half of his life. Referencing Local 213’s Minute Books, newspaper articles, collected correspondence, as well as dozens of personal interviews conducted by the author, this book examines the history of IBEW Local 213 in the turbulent years leading up to the Lenkurt strike. In addition to describing these events and their important historical ramifications, author Ian McDonald chronicles how his father helped to rebuild a left faction within the local union. With a focus on the period between 1955 to 1985, this ground-breaking study of a single construction trade union local—its brief post-World War II experience with Communist leadership, well-known work-site militancy, and repeated interventions by the IBEW’s International Office—sheds light on the local’s “red” minority activism and ultimately explains why McDonald returned to the world of sport to finish his career. --Publisher's description

After the Pandemic: Lasting Effects of COVID-19 on Work and Unpaid Domestic Labour - Peterson, Chris L. (Routledge, 2026)
Presenting a sociological perspective on globalisation and COVID-19 impacts, this book examines the lasting effects of COVID-19 on the structure of work and unpaid domestic labour.Labour patterns have influenced political, social, and economic spheres that affect organisational practices. Following the COVID-19 pandemic, this book showcases these effects upon household labour, care work, unpaid domestic work, and organisational practices, with attention to systemic inequalities by gender and age, net zero, privacy, and digitisation transitions. It examines the exponential post-pandemic growth of digitisation and what this has meant in encouraging remote, home-working or hybrid work health, and wellbeing. Taking a sociology of work approach with a critical eye for neoliberalism influences, this book explores the first years of the pandemic’s aftermath, analysing both its short-term and potential long-term effects on paid work and unpaid domestic labour.This book will be of interest to academics, students, and practitioners in the areas of sociology, global studies, occupational health, and international relations. In particular, those engaged with the sociology of work and the sociology of family will find this a valuable resource for understanding work in the post-pandemic world. --Publisher's description

Weather and Work: How Climate Change Relates to Workers' Rights - Sukdeo, Vanisha (Irwin Law, 2026)
This book investigates the growing impact of climate change on Canadian workers, particularly those in outdoor occupations, who face increasing exposure to extreme conditions such as heat domes and wildfires. The book highlights the urgent need for collaboration between labour and corporate law, governments, businesses, and trade unions to address the unique risks encountered by these workers.Focusing on the Canadian context while drawing on global perspectives, the book examines the role of corporations as employers responsible for protecting their workers. It explores how existing legal frameworks can be adapted to address climate-related risks, as well as the potential for creating new tailored legal solutions. The book also highlights the importance of extralegal mechanisms, particularly corporate social responsibility, in enhancing worker safety in the face of climate change. As the nature of all work is made more hazardous at the hands of climate catastrophe, lawyer and pioneering scholar Vanisha H. Sukdeo uncovers the urgency for legal labour reform. By critiquing current legal approaches and proposing innovative solutions, Weather and Work illustrates how labour and corporate law can work together to protect some of the most vulnerable workers from the growing threats posed by global warming. --Publisher's description

From Streets to Suites: The Sex Trade in the Prairie Cities of Canada at the Turn into the 21st Century Book 1: Around the World in $exy Ways--and Then Back Home - Thatcher, Richard (iUniverse, 2026)
The book describes the contemporary sex trade and its causes and consequences as it has manifested in the cities of Canada's prairie provinces. It concludes with recommendations for a realistic public policy and programming framework to guide the future development of a sexual services sector and to regulate its ongoing operations

The Labour of Care: Canada's Health Care Workers, 1945-2020 - Twohig, Peter L. (Osgoode Society for Canadian Legal History, 2026)
To be published: July 2026. The Labour of Care is the first national, comparative history of health care work. In this book, historian Peter L. Twohig analyses the responses of governments, employers, professional groups, training programs , and unions to the challenge of staffing Canada’s health care system and the reorganization of care.Through careful archival analysis, Twohig demonstrates the conditions under which employees’ boundaries become more flexible, the paths to health care work expand, and tensions emerge among workers in response to labour shortages, decreased funding, and health care reform. This book is attentive to the various identities of health care workers, as women, professionals, union members, and more. It also situates these developments within broader social, economic, and policy changes that reshaped Canada’s health care landscape in the second half of the twentieth century. Examining health care workers in this way reveals a new history of health care that highlights the experiences and contributions of a wide range of workers whose voices have not yet been heard. --Publisher's description